Characterization of the roundness degree of graphite nodules in ductile iron: A new discrete measure independent to resolution (Superficies y Vacío, 2013)
The morphology of graphite nodules in ductile iron, currently controlled by means of chemical inoculants and solidifi cation process, is strongly related to mechanical properties of this material. In fact, the quality of the ductile iron is better when the shape of the graphite particles is rounded. In this article, a new discrete method to measure and to characterize the roundness degree of graphite particles is proposed. This measure takes into consideration the dominant geometry of the nodules and avoids the use of parameters such as area, perimeter and Ferret’s diameter which differs among the systems. In order to show the performance of this measure, it is compared with three measures: Roundness factor, the mean roundness and radius ratio. After comparing with these measures, it was observed that the proposed measure is not affected by the abrupt changes in the contours nor by the shape resolution.